2020
DOI: 10.20944/preprints202004.0181.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-Angiogenesis and Immunotherapy: Novel Paradigms to Envision Tailored Approaches in Renal Cell-Carcinoma

Abstract: Although decision making strategy based on clinico-histopathological criteria is well established, renal cell carcinoma (RCC) represents a spectrum of biological ecosystems characterized by distinct genetic and molecular alterations, diverse clinical courses and potential specific therapeutic vulnerabilities. Given the plethora of drugs available, the subtype-tailored treatment to RCC subtype holds the potential to improve patient outcome, shrinking treatment-related morbidity and cost. The emerging knowledge … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 93 publications
(131 reference statements)
0
21
0
Order By: Relevance
“…In 2020, there are more than 431,000 new cases and 179,000 deaths from kidney cancer in the world [3]. Kidney renal clear cell carcinoma (KIRC), the most common histological subtype, is characterized by extensive tumor heterogeneity, distinct clinical courses, and potential specific treatment vulnerabilities [4]. Genetic alterations occur frequently in KIRC, such as somatic mutations of VHL, PBRM1, SETD2, BAP1, KDM5C,…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, there are more than 431,000 new cases and 179,000 deaths from kidney cancer in the world [3]. Kidney renal clear cell carcinoma (KIRC), the most common histological subtype, is characterized by extensive tumor heterogeneity, distinct clinical courses, and potential specific treatment vulnerabilities [4]. Genetic alterations occur frequently in KIRC, such as somatic mutations of VHL, PBRM1, SETD2, BAP1, KDM5C,…”
Section: Introductionmentioning
confidence: 99%
“…e results from drug sensitivity analysis revealed that low PIK3CA is resistant to 19 small molecules or drugs, demonstrating that PIK3CA is a promising biomarker for drug screening. Indeed, a decision-making strategy based on clinicalhistopathological criteria had been developed for renal cell carcinoma, and we could predict the prognosis of patients based on the subtype so that different drugs or treatment regimens can be selected for therapy, reducing treatmentrelated complications [6]. We should identify more reliable predictive biomarkers of treatment individual sensitivity or resistance, thus prompting precise and individualized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…e pathogenesis of KIRC is extremely complex, involving multiple genes at multiple steps. Moreover, there are no credible predictive markers for the prognosis and treatment of individual sensitivity or resistance in renal cell carcinoma, though some prognostic factors associated with the survival of RCC patients have been described [6,7]. Hence, the identification of new drug targets for KIRC by exploring gene networks for changes associated with tumorigenesis and progression has become the focus of numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the combination of nivolumab + ipilimumab in the CheckMate-214 study showed a 42% ORR compared to 26% in the sunitinib arm. In the same study, the immunotherapy combination obtained a median OS gain of 20 months compared to the sunitinib arm (47 versus 26.6 months, respectively) ( 58 ).…”
Section: Introductionmentioning
confidence: 95%
“…Both studies highlighted a difference between the IMDC prognostic groups, showing that the intermediate- and high-risk groups tended to benefit more from immunotherapy, contrary to what happens in good prognosis cases, which appear to do better with oral TKIs ( 58 ). Recently, McDermott et al evaluated the impact of immunotherapy according to the IMDC risk criteria, selecting a heatmap of genes previously established as angiogenesis-related and immune biology-related genes.…”
Section: Introductionmentioning
confidence: 99%